Fe3+-Exchanged Titanate Nanotubes: A New Kind of Highly Active Heterogeneous Catalyst for Friedel-Crafts Type Benzylation. (25th August 2015) - Du, Yunchen; Guo, Di; Xiong, Meiling; Qi, Yanwu; Cui, Chenkui; Ma, Jun; Han, Xijiang; Xu, Ping
Abstract : Heterogeneous catalysis for Friedel-Crafts type benzylation has received much attention in recent years due to its characteristic of environmental benefits. In this paper, titanate nanotubes (TNTs) were employed as heterogeneous catalyst support, and a new kind of Fe 3+ -exchanged titanate nanotubes (Fe-TNTs) catalyst with highly dispersed ferric sites was constructed by an ion exchange technique. The obtained catalyst was systematically characterized by XRD, TEM, N2 adsorption, XPS, and UV-vis spectra. As expected, Fe-TNTs showed excellent catalytic activities in the benzylation of benzene and benzene derivatives. The recycling tests for Fe-TNTs were also carried out, where the reason for the gradually decreased activity was carefully investigated. Superior to some reported catalysts, the catalytic ability of used Fe-TNTs could be easily recovered by ion exchange again, indicating that Fe-TNTs herein were a highly active and durable heterogeneous catalyst for Friedel-Crafts type benzylation. These results might be helpful for the design and preparation of novel heterogeneous catalysts by combining the structural advantages of titanate nanotubes and active metal ions.